KEAMANAN NASIONAL: ANTARA TEORI DAN PRAKTEKNYA DI INDONESIA1 - Sidratahta Mukhtar (Sociae Polites, 2011)
AbstractThe new design of national security system is urgent to be formulated in facing newvarious typology of threats either conventional or non-conventional in its characteristic.Efforts to reform national security sector have their own obstacles and the ideal nationalsecurity system only could be achieved if there are rule of law, policy developmentcapability, professional implementor, effective supervision and transparent and professionalbudget management.Keywords: National Security, National Secutity Law, National Security Reformation